Involvement of calreticulin in cell proliferation, invasion and differentiation in diallyl disulfide-treated HL-60 cells - Yi, Lan (Oncol Lett, 2016)
Diallyl disulfide (DADS) has shown potential as a therapeutic agent in various cancers. Previously, calreticulin (CRT) was found to be downregulated in differentiated HL-60 cells treated with DADS. The present study investigated the role of CRT proteins in DADS-induced proliferation, invasion and differentiation in HL-60 cells. The present study demonstrated that DADS treatment significantly changed the morphology of HL-60 cells and caused the significant time-dependent downregulation of CRT. Small interfering RNA (siRNA)-mediated knockdown of CRT expression significantly inhibited proliferation, decreased invasion ability, increased the expression of cluster of differentiation (CD)11b and reduced the expression of CD33 in DADS-treated HL-60 cells. DADS also significantly affected cell proliferation, invasion and differentiation in CRT-overexpressed HL-60 cells. Nitroblue tetrazolium (NBT) reduction assays showed decreased NBT reduction activity in the CRT overexpression group and increased NBT reduction in the CRT siRNA group. Following treatment with DADS, the NBT reduction abilities in all groups were increased. In conclusion, the present study clearly demonstrates the downregulation of CRT during DADS-induced differentiation in HL-60 cells and indicates that CRT is involved in cell proliferation, invasion and differentiation in DADS-treated HL-60 cells.